Diversity and genetic potential of various morphological traits among common bean (Phaseolus vulgaris, Fabaceae) landraces - Tura Bareke (Society for Indonesian Biodiversity, 2019)
Abstract. Bareke T. 2019. Diversity and genetic potential of various morphological traits among common bean (Phaseolus vulgaris, Fabaceae) landraces. Biodiversitas 20: 3237-3245. The study was undertaken to identify the morphological diversity and genetic potential among landraces of common bean (Phaseolus vulgaris L.) at field conditions of Adama District, Ethiopia. Twenty four common bean landraces from different agroecological zones were collected and grown in three replications. Data of eight agromorphological descriptors were collected using IBPGR protocol. Accordingly, Zale wehy was significantly different (p<0.05) from all landraces with the highest mean number of pods per plant. On the other hand, the mean number of seeds per pod was significantly (p<0.05) higher for Dobole followed by Dima, Kalibushay and Adi tikko while Logoma dume has the lowest number of seeds per pod. The average number of seeds per pod had inverse relationship with seed size. The highest diversity was found in number of seed per plant among landraces while the lowest diversity was found in number of seed per pod. Based on morphological traits similarities among 24 landraces were classified into 4 major categories. Heritability was the highest for seed length (0.97) followed by number of seed per pod (0.94) and seed per plants (0.69) and the lowest (0.1) for height of plant and the rest found between these values. The variability observed in seed length, number of seeds per pod, number of seeds per plant and number of pods per plant which could be utilized in variety improvement programs. Therefore, crop breeders could give emphasis to these traits of landraces to monitor and use for the breeding program, future production and for other domestic purposes.